2000
DOI: 10.1016/s0010-2180(99)00119-4
|View full text |Cite
|
Sign up to set email alerts
|

Postflame reaction chemistry of dichloromethane: variations in equivalence ratio and temperature

Abstract: We report on the destruction pathways and byproduct formation of dichloromethane (CH 2 Cl 2 ) in conditions typical of incinerator postflame regions (injection temperature ϭ 900 -1200 K; equivalence ratio ϭ 0.6, 0.9, 1.0, 1.1; residence time ϭ 0.28 -0.35 s). This is the first study to independently vary equivalence ratio and temperature, and evaluate their impacts on byproduct yield and destruction efficiency. We inject 750 ppm CH 2 Cl 2 into postflame combustion products and measure byproducts with extractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the glow discharge experiment, the reactions in the two reactors were carried out under the same vacuum and sharing the same electrical power source but were fed different starting reactants. In reactor I, the reactant was chloroform vapor, while the reactants in reactor II were composed of variety of volatile chlorinated carbon species formed in the preceding reactor, such as C 4 or C 6 . The experimental evidence suggested the possibility of designing the proper precursors so as to improve fullerene yield in the synthetic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the glow discharge experiment, the reactions in the two reactors were carried out under the same vacuum and sharing the same electrical power source but were fed different starting reactants. In reactor I, the reactant was chloroform vapor, while the reactants in reactor II were composed of variety of volatile chlorinated carbon species formed in the preceding reactor, such as C 4 or C 6 . The experimental evidence suggested the possibility of designing the proper precursors so as to improve fullerene yield in the synthetic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Incineration is an attractive technology due to volume reduction, detoxification of wastes and heat and materials recovery [3][4][5]. Previous studies have shown that chlorinated hydrocarbons flames have lower flame velocities and that toxic products of incomplete combustion are formed [4,[6][7][8][9][10][11][12]. To use this technology safely, it is important to understand the combustion characteristics of chlorinated hydrocarbons and the influence of chlorinated hydrocarbons on the combustion chemistry of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…There are several similarities in the product distribution reported by these researchers and in the results obtained in the present study. For instance, the product distribution reported by Srgo et al included species such as C 2 HCl 3 , C 2 H 3 Cl, cis and trans C 2 H 2 Cl 2 , CHCl 3 , C 2 H 2 , C 2 H 4 and HCl [6,8] .…”
Section: Ho Et Al and Srgo Et Al Examined Dcm Decomposition Via Thementioning
confidence: 99%
“…Prior investigations on DCM decomposition involved the study of various process parameters and reaction conditions, such as addition of hydrogen/oxygen mixtures, oxidative pyrolysis and the effect of temperature and equivalence ratio, using high temperature technologies [6][7][8]. In the plasma field, various technologies such as RF, pulsed corona and DBD have been employed to investigate DCM decomposition, using carrier gases such as nitrogen, air and argon under varying experimental conditions [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%